ANALISISRISIKO PASCA PANEN TANDAN BUAH SEGAR (TBS) KELAPA SAWIT PETANI PERKEBUNAN INTI RAKYAT (PIR) DI DESA PAGARUYUNG KECAMATAN TAPUNG KABUPATEN KAMPAR - Andaya, Olgi; Hadi, Syaiful; Yusri, Jumâ€™atri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to know the result of large production loss, to analyze the probability and impacts of lost production at post harvest process of the fresh fruit bunches (FFB) paml oil from on land until to palm oil factory (POF). Research was done by survey at Pagaruyung Village. Data were collected from 30 small-holders palm oil farmers using purposive sampling. Analysis of the results obtained shows that the loss of production the fresh fruit bunches (FFB) palm oil in post harvest process as 4,91 percent/2ha/month, that loss of production at land as 0.93 percent, at TPH ( FFB raw ) as 0.36 percent, at TPH (FFB) as 0.36 percent and at palm oil factory (Sorting plant process) as 2.93 percent. Probability of the loss production at land as 25.18 percent, at TPH (FFB raw and FFB) as 23.18 percent and 23.24 percent, at palm oil factory (sorting plant process) as 18.79 percent. The impact of the losses arising from the loss of post-harvest TBS is Rp 190.137,97/2ha/month and if combined for one year will reach Rp 2.281.655,60.Â Keywords:Palm Oil, Analysis Of The Risk, Post-harvest